2013
DOI: 10.1116/1.4838295
|View full text |Cite
|
Sign up to set email alerts
|

Picosecond electrical switching of single-gate metal nanotip arrays

Abstract: Articles you may be interested inElectron beam collimation from an all-metal double-gate 40 000 nanotip array: Improved emission current and beam uniformity upon neon gas conditioning

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Figure 2a shows the field emission characteristics between the current I detected at a counter electrode (anode) and the electron extraction potential V ge applied between G ex and emitters E . This relationship was measured in the DC gun test setup740, shown in Fig. 3a, with the nominal background pressure <5 × 10 −9  mbar.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…Figure 2a shows the field emission characteristics between the current I detected at a counter electrode (anode) and the electron extraction potential V ge applied between G ex and emitters E . This relationship was measured in the DC gun test setup740, shown in Fig. 3a, with the nominal background pressure <5 × 10 −9  mbar.…”
Section: Resultsmentioning
confidence: 93%
“…4, we show the cathode image at L =0 for 40 keV beam energy, as detected by reducing the solenoid current by 10% from the focussing condition. The granular pattern, that is typical for FEAs without neon gas conditioning745, indicated that not all emitters were active. The effect of the beam collimation was visible as the narrowing of the beamlet spots by increasing k col from 0 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations